2013
DOI: 10.1007/s11846-013-0117-1
|View full text |Cite
|
Sign up to set email alerts
|

Technological alliance portfolio configuration and firm performance

Abstract: Firms pursuing technological alliances to gain competitive advantages have become a ubiquitous phenomenon in today's business environment. This article examines which technological alliance portfolio configuration is better for focal firm performance using a portfolio rather than a dyadic perspective. To assess technological alliance portfolio effects on Korean pharmaceutical and biotechnology firms, we adopted three explanatory variables-number of alliances, number of partners, and spanning structural holes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
0
15
0
2
Order By: Relevance
“…The existing literature on innovation emphasizes the unique role of boundary-spanning search in organizational innovation activities [8,33]. First, it increases the resource stock or portfolio of an enterprise and facilitates innovation activities [34][35][36][37]. Second, Lopez-Vega, Tell, and Vanhaverbeke (2016) [15] opine that enterprises in need of specific technology can link up with external suppliers through boundary-spanning search to provide technical and scientific solutions to enhance competitive advantage and innovation capability.…”
Section: The Mediating Role Of Network Tiesmentioning
confidence: 99%
“…The existing literature on innovation emphasizes the unique role of boundary-spanning search in organizational innovation activities [8,33]. First, it increases the resource stock or portfolio of an enterprise and facilitates innovation activities [34][35][36][37]. Second, Lopez-Vega, Tell, and Vanhaverbeke (2016) [15] opine that enterprises in need of specific technology can link up with external suppliers through boundary-spanning search to provide technical and scientific solutions to enhance competitive advantage and innovation capability.…”
Section: The Mediating Role Of Network Tiesmentioning
confidence: 99%
“…Therefore, this study adopted two size variables (NOA and NOP) and showed not only that these two variables vary significantly as the degree increases from a focal firm (where the correlations between the NOA and the NOP at one degree and at the extended APC are 0.72 and 0.63, respectively), but also that they have a different effect on firm innovation. This difference is due to the repeated partnerships of the two firms' alliances (Kim & Choi, 2014a). Network theory states that the NOA in a focal firm's APC represents the number of ties, while the NOP represents the number of nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies examining APC size have been focused on one aspect of size, which is NOA, while ignoring a second important dimension, which is NOP. Therefore, this study addresses the size of APC with NOP included, since it is theoretically different from NOA (Kim & Choi, 2014a). In the extended APC, it is necessary for the integrated size (NOA and NOP) to positively affect innovation performance for up to three degrees.…”
Section: Size Of the Extended Apcmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Song, 2007;Kim and Choi 2014;Ma et al 2013). However, this study analyzes the configuration of alliance portfolio using the patent citation information and various patent cation indexes.…”
Section: Configuration Of Alliance Portfoliomentioning
confidence: 99%